Smoothened loss is a characteristic of neuroendocrine prostate cancer. Issue 9 (6th May 2021) - Wang, Lili; Li, Haiying; Li, Zhang; Li, Ming; Tang, Qi; Wu, Chunxiao; Lu, Zhiming
Abstract: Purpose: Hedgehog (Hh) signaling promotes castration‐resistant prostate cancer by supporting androgen‐independent prostate cancer cell development and growth; however, its role in neuroendocrine prostate cancer (NEPC) has not yet been explored. In this study, we assessed the expression of key genes involved in Hh signaling in prostate cancer and investigated the potential role of smoothened (SMO) in the pathogenesis of NEPC. Methods: Six public datasets, each containing cases of prostate adenocarcinoma (AdPC) and NEPC, were analyzed to compare the differential messenger RNA (mRNA) expression of six classic Hh signaling genes. The SMO, synaptophysin, chromogranin A (CHGA) and androgen receptor (AR) proteins were evaluated in human tissues from 5 cases of NEPC, 2 cases of AdPC mixed with NEPC, 2 cases of AdPC with neuroendocrine differentiation and 22 cases of high‐grade AdPC as determined by an immunohistochemistry assay. Gene set enrichment analysis (GSEA) was performed to identify relevant genetic signatures associated with SMO expression based on the public datasets. Stable SMO‐knockdown LNCaP and C4‐2B cells were established with a lentiviral system, and the expression of SMO, Gli1, AR, prostate‐specific antigen (PSA), and REST was assessed by real‐time polymerase chain reaction and western blot. Secreted PSA in the conditioned medium was assessed by ELISA. Gli1 was ectopically expressed performed by the transfection of Gli1 complementary DNA into SMO‐knockdown LNCaP cells, and western blot was used to assess of AR and PSA expression. Results: The mRNA level of SMO was dramatically downregulated in NEPC samples compared with AdPC samples in all 6 public datasets. SMO protein loss was observed in 100% of NEPC samples but in only 9% (2 of 22) of high‐grade AdPC samples. GSEA results showed that SMO loss was closely correlated with AR signaling activity. Stable SMO knockdown significantly attenuated AR signaling activity and suppressed AR expression, while Gli1 overexpression partially reversed the inhibitory effects of SMO knockdown on AR signaling activity and AR expression in LNCaP and C4‐2B cells. Conclusion: These results demonstrate that SMO loss is a characteristic of NEPC and that detecting SMO by IHC could aid pathologists in NEPC diagnosis. SMO loss may promote NEPC pathogenesis by modulating AR signaling.